Hydrodynamic model intercomparison for the patos lagoon (Brazil) - Martins, Flávio Augusto Bastos da Cruz (2009)
An intercomparison study is carried out between two models with different formulations and spatial discretizations in order to overcome the limitations posed by the standard calibration and validation procedures and improve confidence in the hydrodynamic results for the Patos Lagoon. Numerical simulations were carried out applying the TELEMAC and MOHID models, based on the same boundary conditions and identical calibration coefficients so differences in calculated flow conditions result from the formulations and parameterizations of each model. Results from both models are compared with measurements from three stations inside the lagoon. Preliminary results indicate that both models compare well with the measurements and with each other. These results increase the confidence on hydrodynamic results for the Patos Lagoon and provide the first step towards water quality studies for the area.